Uncertainty and the use of force among Venezuelan police officers - Gabaldón, Luis Gerardo (Crime, law and social change, 2009)
Literature often emphasizes the use of force as a distinctive feature of police work, while risky encounters and uncertainty are conditions under which such work is carried out daily. Conditions leading to the use of force by the police have been associated with the presence of menacing minorities, losing verbal control, the youth and lack of experience of officers, and critical physical proximity between officers and suspects. Additionally, defiance towards the police has often been linked to increased force used by the police. It is here proposed that uncertainty also fosters police officers’ dispositions to use force. In this study, four focus groups were conducted with officers from two Venezuelan municipal police departments in October 2003, presenting a hypothetical scenario progressing from contact with suspects towards an open confrontation involving a shooting. Officers perceived, through different phases of the scenario, an encounter of no easily predictable outcome with suspects, involving potential harm to the police and bystanders. A pattern seemed to appear among officers in which overcoming real or assumed resistance became the central issue. When physical confrontation with suspects became evident, self defence was the clearest justification for the use of force, though the use of force was also defended by officers without further elaboration on the requirements and conditions for effectively thwarting aggression. It appears that uncertainty about the outcome of a situation fosters both the disposition and the justification for using force.